2022
DOI: 10.3390/agronomy12071642
|View full text |Cite
|
Sign up to set email alerts
|

Response of Nitrifier and Denitrifier Abundance to Salinity Gradients in Agricultural Soils at the Yellow River Estuary

Abstract: Salinization is considered a threat to agricultural soil and decreases crop yield worldwide. Nitrification and denitrification are the core processes of soil N-cycle. However, the response of nitrifiers and denitrifiers to salinity in agricultural soils remains ambiguous. The study aimed to explore the effect of salinity on nitrifiers and denitrifiers communities in agricultural soils along a naturally occurring salinity gradient. The effects of salinity on the abundance, composition, and interactions of nitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…The N min release rate is strongly dependent on both the biodegrability of N org and environmental factors affecting microbial activity. These issues are discussed in detail in this section [11][12][13].…”
Section: Microorganisms Activity: Availability Of Soil Nitrogenmentioning
confidence: 99%
See 1 more Smart Citation
“…The N min release rate is strongly dependent on both the biodegrability of N org and environmental factors affecting microbial activity. These issues are discussed in detail in this section [11][12][13].…”
Section: Microorganisms Activity: Availability Of Soil Nitrogenmentioning
confidence: 99%
“…Therefore, a question arises with respect to the extent to which this factor affects nitrification and denitrification, key components of the N cycle. This issue was studied in the soils of the Yellow River Estuary (China), evaluating the response of nitrifying and denitrifying microorganisms to a salinity gradient [13]. It was clearly found that increased salinity significantly reduced the abundance of nitrifiers.…”
Section: Microorganisms Activity: Availability Of Soil Nitrogenmentioning
confidence: 99%
“…AOA has been found to occupy higher abundances than AOB in many studies [51][52][53][54]. AOA and AOB respond differently to factors such as pH, salinity, NH 4 + , and NO 3 − [55]. AOA is better adapted to low NH 4 + concentrations, and it has higher abundance at higher NO 3 − concentrations, while AOB tends to have a higher abundance at higher NH 4…”
Section: Nitrogen Conversion-related Microorganismsmentioning
confidence: 99%